A low-cost and efficient participatory ergonomic intervention to reduce the burden of work-related musculoskeletal disorders in an industrially developing country: an experience report - Bernardes, Joao Marcos [UNESP]; Ruiz-Frutos, Carlos; Moro, Antonio Renato Pereira; Dias, Adriano [UNESP] (Taylor & Francis Ltd, 2020)
Work-related musculoskeletal disorders (WMSDs) are the first cause of occupational illness in Brazil and the number of cases in the industrial sector has increased progressively in the last 6 years. In order to prevent WMSDs, workplace ergonomics interventions are frequently implemented worldwide. This article describes the implementation strategy of a participatory ergonomic intervention conducted in the quality control department of a medium-sized Brazilian garment company. The intervention was carried out based on the nine steps presented by Vink, Imada and Zinck, and workers' exposure to risk factors was investigated using the rapid upper limb assessment method. A low-tech and low-cost solution that successfully reduced workers' exposure to WMSD risk factors was proposed, prototyped, tested and, finally, introduced. Participatory ergonomic interventions can be a feasible and effective approach to reduce the exposure to work-related risk factors for WMSDs in industrially developing countries.
Keywords: cumulative trauma disorders; ergonomics; participatory ergonomics; developing countries; case reports